2013
DOI: 10.1007/s13197-013-1106-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying level of dried milk proportion on formulation and reconstitution of Phirni mix powder

Abstract: An investigation was undertaken to study the varying proportion of WMP to SMP (25:75, 50:50 and 75:25) for formulation of Phirni mix powder (PMP). The sensory quality of experimental Phirni increased consistently with the increase in the levels of WMP upto 50:50, thereafter, decreased significantly (p<0.01). The maximum sensory scores were obtained with a proportion of 50:50 for all sensory attributes. The textural characteristics were found significant (p<0.01) with the increase in the proportion of WMP. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Also, increment in cooking time significantly increased ( p < .05, Table 4) the visual consistency score of the samples. Kumar, Paul, and Kumar (2015) reported that rheological characteristics of phirni like hardness increased with the increase in the period of cooking at 85 ± 5°C. It is a well‐known fact that as the cooking time of kheer preparation increased, the hardness of vermicelli decreased, which is more acceptable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, increment in cooking time significantly increased ( p < .05, Table 4) the visual consistency score of the samples. Kumar, Paul, and Kumar (2015) reported that rheological characteristics of phirni like hardness increased with the increase in the period of cooking at 85 ± 5°C. It is a well‐known fact that as the cooking time of kheer preparation increased, the hardness of vermicelli decreased, which is more acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…Increased cooking of rice grains led to an increase in the level of total solids which further decreased hardness, thus leading to softening of rice grains (Kavimani, Barnwal, Minz, & Dodeja, 2016). Kumar et al (2015) reported that rheological characteristics of phirni like adhesiveness increased with the increase in the period of cooking at 85 ± 5°C. Jafri, Jha, Rasane, and Sharma (2015) reported that the processing time had a negative and significant ( p < .01) effect on grain integrity.…”
Section: Resultsmentioning
confidence: 99%